Cheshire's Modern law of real property - Cheshire, G. C (Butterworth, 2000)
Since the publication of the last edition in 1994, there have been major developments in this area of the law. In addition to the numerous judicial decisions, important legislative changes have also been incorporated; these include the Agricultural Tenancies Act 1995 the Landlord and Tenant (covenants) Act 1995, the Trusts of Land and Appointment of Trustees Act 1996, the Housing Act 1996, the Land Registration Act 1997 and the Contracts (Rights of Third Parties) Act 1999. The various Reports of the Law Commission have also been incorporated, including the far-reaching Consultative Document on Land Registration for the Twenty-First Century